Human Resource Management in Improving the Quality of Superior Potential - Silvia Angelica; M. Chaerul Risky; Daud Arifin; Anggi Novenda; Nadine Azzahra (TALENTA Publisher, Universitas Sumatera Utara, 2026)
Organizations in the digital era face increasing pressure to develop superior human resources as a source of sustainable competitive advantage; however, many organizations still implement Human Resource Management (HRM) practices in a fragmented and non-integrated manner, resulting in suboptimal organizational performance. This study aims to analyze the strategic role of integrated HRM practices in building superior human resource potential within organizations. A qualitative literature review method was employed, utilizing content analysis of 20 indexed journal articles published between 2015–2025, sourced from Google Scholar, Sinta, and Garuda databases, with inclusion criteria covering relevance, publication recency, and indexing quality. Findings reveal that integrated HRM best practices encompassing competency development, performance-based compensation, transformational leadership, and digital technology utilization consistently outperform contingency and configuration approaches in enhancing superior organizational potential. This study contributes theoretically by reinforcing the Resource-Based View (RBV) framework, demonstrating that strategically integrated HRM practices constitute an inimitable source of competitive advantage, and practically recommends organizations adopt holistic HRM systems aligned with digital-era demands to sustain long-term organizational excellence.